1997
DOI: 10.1007/pl00004997
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac electrophysiological actions of NS-21 and its active metabolite, RCC-36, compared with terodiline

Abstract: Terodiline, an anticholinergic drug with a Ca2+ blocking action, is thought to be associated with torsade de pointes, a serious ventricular tachycardia. NS-21 is a newly developed drug for the treatment of urinary frequency and urinary incontinence and it has pharmacological properties similar to those of terodiline. It remains unknown, however, whether NS-21 and its active metabolite, RCC-36, have any proarrhythmic activity. The electrophysiological properties of NS-21 and RCC-36 were examined in guinea pig v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Terodiline induced a concentration‐dependent reduction in the amplitude of I Ca,L in guinea‐pig ventricular myocytes pulsed to 0 mV at 0.1–0.2 Hz. Data from myocytes bathed and dialysed with K + solutions were best described by a Hill equation with IC 50 of 15.2 μ M , whereas data on Cd 2+ ‐sensitive peak I Ca,L from myocytes investigated under K + ‐free conditions were best described with an IC 50 of 12.2 μ M. The estimate determined under K + conditions is considerably lower than the K 0.5 of 33.5 μ M reported by Hayashi et al . (1997) in a study on guinea‐pig ventricular myocytes under similar (K + , temperature, pulsing rate) experimental conditions.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Terodiline induced a concentration‐dependent reduction in the amplitude of I Ca,L in guinea‐pig ventricular myocytes pulsed to 0 mV at 0.1–0.2 Hz. Data from myocytes bathed and dialysed with K + solutions were best described by a Hill equation with IC 50 of 15.2 μ M , whereas data on Cd 2+ ‐sensitive peak I Ca,L from myocytes investigated under K + ‐free conditions were best described with an IC 50 of 12.2 μ M. The estimate determined under K + conditions is considerably lower than the K 0.5 of 33.5 μ M reported by Hayashi et al . (1997) in a study on guinea‐pig ventricular myocytes under similar (K + , temperature, pulsing rate) experimental conditions.…”
Section: Discussionmentioning
confidence: 69%
“…For example, Larsson‐Backström et al . (1985) found that terodiline inhibited rat papillary muscle contraction with an IC 50 of 18 μ M , and Hayashi et al . (1997) reported that the drug inhibited guinea‐pig ventricular I Ca,L with an IC 50 of 34 μ M .…”
Section: Introductionmentioning
confidence: 96%
“…The effects of 0.03 to 10 μM terodiline on guinea‐pig ventricular I K have been evaluated, and the results indicate that the drug preferentially inhibits the I Kr component of the current. Identification of this mechanism sheds light on the cardiotoxicity of the compound, and helps clarify recent findings of Hayashi et al (1997) on guinea‐pig ventricular myocytes. These investigators measured tail I K at −40 mV after 500 ms depolarizations to positive potentials, and found that 10 μM terodiline reduced the amplitude by ca.…”
Section: Discussionmentioning
confidence: 86%
“…Adverse effects of terodiline on the heart include bradycardia, atrioventricular disturbances, QT prolongation, and malignant ventricular tachycardia (torsades de pointes) (Connolly et al , 1991; McLeod et al , 1991; Stewart et al , 1992; Pressler et al , 1995). Since terodiline inhibits cardiac I Ca,L (Hayashi et al , 1997, Ogura et al submitted; Pressler et al , 1995), it is possible that this is the sole mechanism by which the drug causes bradycardia and atrioventricular block. However, inhibition of I Kr by terodiline may contribute in both a direct and an indirect manner if, as in rabbit nodal tissues (Shibasaki, 1987; Verheijck et al , 1995; Ono & Ito, 1995; Lei & Brown, 1995), partial inhibition of I Kr in human nodal tissues lengthens the action potential, slows the pacemaker rate, and lowers the maximum diastolic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Terodiline has two optical isomers, R- and S-terodiline, which were both present in the racemic terodiline used in our experiments. R-terodiline shows high anticholinergic properties, responsible for the prolongation of FPD 46 , whereas S-terodiline shows calcium antagonist properties 47 . It is likely that the FPD shortening effect of calcium antagonist S-terodiline concealed the FPD prolongation effect of R-terodiline.…”
Section: Discussionmentioning
confidence: 99%